Political-electoral participation of migrants living in Buenos Aires and Mendoza, Argentina - Sander, Joanna; Guzzo, Giuliana (Política. Revista de Ciencia Política, 2023)
This paper studies the political-electoral participation of migrants residing in the provinces of Buenos Aires and Mendoza, Argentina. It uses a methodology that combines primary and secondary sources. The paper is organized into three sections. The first explores the theorization of political rights in their sub-national dimension and the political-electoral participation of migrants in Argentina. Secondly, it analyses and compares the current legal frameworks that enables or restricts migrant voting in the provinces of Buenos Aires and Mendoza. Finally, we analyze the political-electoral participation of migrants according to the results of the 2021 general elections.